Prevention of Postsurgical Abdominal Adhesion Using Electrospun TPU Nanofibers in Rat Model. (28th December 2021) - Gholami, Ahmad; Abdoluosefi, Homeira Emad; Riazimontazer, Elham; Azarpira, Negar; Behnam, Mohamadali; Emami, Farzin; Omidifar, Navid
Abstract : Intra-abdominal adhesions following surgery are a challenging problem in surgical practice. This study fabricated different thermoplastic polyurethane (TPU) nanofibers with different average diameters using the electrospinning method. The conditions were evaluated by scanning electron microscopy (SEM), atomic force microscope (AFM), and Fourier transform infrared spectrometer (FTIR) analysis. A static tensile test was applied using a strength testing device to assess the mechanical properties of the electrospun scaffolds. By changing the effective electrospinning parameters, the best quality of nanofibers could be achieved with the lowest bead numbers. The electrospun nanofibers were evaluated in vivo using a rat cecal abrasion model. The macroscopic evaluation and the microscopic study, including the degree of adhesion and inflammation, were investigated after three and five weeks. The resultant electrospun TPU nanofibers had diameters ranging from about 200 to 1000 nm. The diameters and morphology of the nanofibers were significantly affected by the concentration of polymer. Uniform TPU nanofibers without beads could be prepared by electrospinning through reasonable control of the process concentration. These nanofibers' biodegradability and antibacterial properties were investigated by weight loss measurement and microdilution methods, respectively. The purpose of this study was to provide electrospun nanofibers having biodegradability and antibacterial properties that prevent any adhesions or inflammation after pelvic and abdominal surgeries. The in vivo experiments revealed that electrospun TPU nanofibers reduced the degree of abdominal adhesions. The histopathological study confirmed only a small extent of inflammatory cell infiltration in the 8% and 10% TPU. Conclusively, nanofibers containing 8% TPU significantly decreased the incidence and severity of postsurgical adhesions, and it is expected to be used in clinical applications in the future.